Butterfly Insectarium from Three Different Ecosystems of Gunung Palung National Park as Biology Learning Resource - Nurliza Nurliza; Anandita Eka Setiadi; Hanum Mukti Rahayu (Jurnal Penelitian Pendidikan IPA, 2023)
Gunung Palung National Park (GPNP) has butterfly diversity. However, there is a lack of information about butterflies in Gunung Palung National Park as a learning resource. This article reports on the species of butterflies in three different ecosystems from GPNP and the potential of insectariums as a source of learning biology. There are two stages of research, first to examine the species of butterflies from GPNP in the Freshwater Swamp Forest, Alluvial Forest, and Lowland Granite Forest ecosystems. Second, to examine the potential of butterflies insectariums as a learning resource. The location of the research was determined by purposive sampling. Butterflies are caught by sweeping technique. Collecting data on potential learning resources using observation, documentation, and questionnaires. The results found 119 individuals from 39 butterfies species. Based on the aspects of access, safety, time, cost, clarity of potential, suitability of learning objectives, clarity of material objectives, and clarity of information, it shows that the potential of the butterfly insectarium is worthy of being used as a learning resource, especially in biology subjects, namely Biodiversity, Classification of Living Things, Animalia, and Ecology